Stress mechanism involved in the progression of alcoholic liver disease and the therapeutic efficacy of nanoparticles - Aghara, Hiral; Chadha, Prashsti; Zala, Devangi; Mandal, Palash (Frontiers in Immunology, 2023)
Alcoholic Liver Disease (ALD) poses a significant threat to human health, with excessive alcohol intake disrupting the immunotolerant environment of the liver and initiating a cascade of pathological events. This progressive disease unfolds through fat deposition, proinflammatory cytokine upregulation, activation of hepatic stellate cells, and eventual development of end-stage liver disease, known as Hepatocellular Carcinoma (HCC). ALD is intricately intertwined with stress mechanisms such as oxidative stress mediated by reactive oxygen species, endoplasmic reticulum stress, and alcohol-induced gut dysbiosis, culminating in increased inflammation. While the initial stages of ALD can be reversible with diligent care and abstinence, further progression necessitates alternative treatment approaches. Herbal medicines have shown promise, albeit limited by their poor water solubility and subsequent lack of extensive exploration. Consequently, researchers have embarked on a quest to overcome these challenges by delving into the potential of nanoparticle-mediated therapy. Nanoparticle-based treatments are being explored for liver diseases that share similar mechanisms with alcoholic liver disease. It underscores the potential of these innovative approaches to counteract the complex pathogenesis of ALD, providing new avenues for therapeutic intervention. Nevertheless, further investigations are imperative to fully unravel the therapeutic potential and unlock the promise of nanoparticle-mediated therapy specifically tailored for ALD treatment.